Pengaruh Faktor Lingkungan terhadap Karakteristik Agronomi Kopi Robusta pada Dua Tipe Penaung dalam Sistem Agroforestri - Nilasari Dewi; Ken Ilmaya Chairani (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
Coffee plants are one of the plantation crops cultivated in Indonesia. Coffee cultivation is generally carried out in agroforestry systems with shade plants such as rubber and sengon. The type of shade planted in coffee cultivation can affect temperature, humidity, and light intensity, all of which can influence the agronomic characteristics of coffee plants. This study aimed to analyze the effects of temperature, humidity, and light intensity on the agronomic characteristics of coffee plants grown under two types of shade in the agroforestry system. The research was conducted by measuring temperature, humidity, light intensity, and the agronomic characteristics of coffee plants in each observation plot. The data obtained were analyzed using SEM analysis and correlation methods. The average temperature in the agroforestry areas with rubber and sengon was 29.30˚C and 29.42˚C, respectively. The average humidity in the agroforestry areas with rubber and sengon shade was 65.72% and 64.76%, respectively. The average light intensity in the agroforestry areas with rubber shade was 35.79%, while in the sengon shade, it was 45.36%. Temperature and light intensity in both agroforestry systems exhibit a positive correlation with the number of productive branches and stomatal density of coffee plants. In contrast, humidity shows a negative correlation with chlorophyll content.